Realization of Ternary Sigma-Delta Modulated Arithmetic Processing Modules. (16th March 2009) - Sadik Sadik, Amin Z. Amin Z.; O'Shea O'Shea, Peter J. Peter J.
Abstract : Sigma-delta modulated systems have a number of very appealing properties and are, therefore, heavily used in analog to digital converters, amplifiers, and modulators. This paper presents new results which indicate that they may also have significant potential for general purpose arithmetic processing. The paper introduces new arithmetic processing structures for ternary (i.e., +1, 0, or − 1 ) sigma-delta modulated signals. Simulations show that these new structures can be implemented very efficiently and have relatively good accuracy.